Money Stock Control and Inflation Targeting in Germany A State Space Modelling Approach to the Bundesbank’s Operating Procedures and Intermediate Strategy - Brand, Claus (Contributions to Economics, 2001)
The book considers issues relevant to the European Central Bank in refining and communicating its strategy. It offers a historical assessment of the Bundesbank's strategy of monetary targeting conducted from 1974 to 1998. In contrast to several other prominent studies it is argued that money played a flexible but very important role in the conduct of its policy. It also explores the implications of the identified monetary policy regime in the context of various theories of the money supply process. The empirical analysis conducted in this study is based on a linear state space modelling approach which offers an appealing and direct representation of common stochastic trends. The framework is less restrictive and it is encompassing in that it does not construe the persistent dynamics as being driven by pure random walk components